Pengaruh Literasi Digital dan Gaya Belajar terhadap Prestasi Akademik Mahasiswa di Era Pembelajaran - darmawan, Roslinda jasmine; Dara, Satria Danur; Adiba; Junengsih (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This study aims to analyze the influence of digital literacy and learning styles on students' academic achievement in the era of technology-based learning. The study used a quantitative approach with a purposive sampling technique on 110 student respondents who had experience attending online lectures. Data collection was carried out through questionnaires and analyzed using SPSS 25 software. The results showed that both digital literacy and learning styles had a positive and significant influence on students' academic achievement, both partially and simultaneously. These findings indicate that students' ability to access, understand, and use digital technology, as well as awareness of their personal learning styles, greatly determines academic success in the modern learning era.